2007
DOI: 10.1152/physiolgenomics.00011.2007
|View full text |Cite
|
Sign up to set email alerts
|

MyD88-dependent changes in the pulmonary transcriptome after infection withChlamydia pneumoniae

Abstract: , an intracellular bacterium, causes pneumonia in humans and mice. Toll-like receptors and the key adaptor molecule myeloid differentiation factor-88 (MyD88) play a critical role in inducing immunity against this microorganism and are crucial for survival. To explore the influence of MyD88 on induction of immune responses in vivo on a genome-wide level, wildtype (WT) or MyD88 Ϫ/Ϫ mice were infected with C. pneumoniae on anesthesia, and the pulmonary transcriptome was analyzed 3 days later by microarrays. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 70 publications
(68 reference statements)
4
28
0
Order By: Relevance
“…Previous studies have shown a role for this protein in other infections such as Salmonella (42, 43), Chlamydia (44), and Mycobacterium tuberculosis (45, 46) and have similarly attributed the induction of lipocalin 2 to TLR-dependent signaling and subsequent T cell activation pathways. Indeed, we have recently confirmed the ability of Th17 cytokines, IL-17 and IL-22 to induce Lcn2 and inhibit Klebsiella in an in vitro model (18).…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies have shown a role for this protein in other infections such as Salmonella (42, 43), Chlamydia (44), and Mycobacterium tuberculosis (45, 46) and have similarly attributed the induction of lipocalin 2 to TLR-dependent signaling and subsequent T cell activation pathways. Indeed, we have recently confirmed the ability of Th17 cytokines, IL-17 and IL-22 to induce Lcn2 and inhibit Klebsiella in an in vitro model (18).…”
Section: Discussionmentioning
confidence: 95%
“…Reduction of NO production upon incomplete iNOS inhibition abolishes susceptibility of C57BL/6 mice to Chlamydia -induced disease. Thus, the quantity of NO released by infected macrophages seems to define pathogenic versus protective macrophage responses to chlamydial infection (17). …”
Section: Role Of Arginase In Alveolar Macrophages During Pulmonary Inmentioning
confidence: 99%
“…However, in the never-ending battle for iron between pathogen and host, the immune system counters by producing siderocalin (also known as lipocalin 2 and neutrophil gelatinase-associated lipocalin, NGAL), a protein that is upregulated as part of the acute-phase response to infection, and that binds specifically to some siderophores to disrupt pathogen iron acquisition [52,53] . Siderocalin is secreted by neutrophils, macrophages and other cell types following infection by a number of different organisms, and in some cases Toll-like receptors (TLRs) have been shown to be involved in this response [42,[54][55][56][57] . Siderocalin knockout mice have compromised immunity to pathogenic E. coli and to M. tuberculosis , displaying elevated tissue bacterial numbers and decreased survival following infection with these organisms [54,58,59] .…”
Section: Expression Of Secreted Iron-binding Proteinsmentioning
confidence: 99%